Association of Circulating 25(OH)D and Lower Urinary Tract Symptoms: A Four-Year Prospective Study among Elderly Chinese Men - Liu, Zhao-Min (Nutrients, 2016)
The role of vitamin D in relation to lower urinary tract symptoms (LUTS) remains inconclusive. This four-year longitudinal study aims to explore the association of circulating 25(OH)D and LUTS in elderly Chinese men. Two thousand Chinese men aged 65 and older were recruited from a local community, of which 1998 (99.9%) at baseline and 1564 (78.2%) at four-year follow-up reported data on LUTS, and 988 of the randomly chosen subpopulation were assayed for serum 25(OH)D by radioimmunoassay at baseline. LUTS were evaluated by a validated International Prostate Symptoms Scale (IPSS). Data on demographic characteristics, lifestyle factors, health, and medications were collected. Serum parathyroid and sex steroid hormones and genotypes of vitamin D receptors were assayed. The association of serum 25(OH)D and LUTS was examined by using multivariable regression models. Serum 25(OH)D was not significantly associated with the changes of IPSS or the risk of LUTS in overall participants. However, among men with 25(OH)D ≤ 60 nmol/L, each 10 nmol/L increase of 25(OH)D over 0 nmol/L was significantly associated with 1.3 lower points of IPSS or a 51.6% decreased risk for moderate/severe LUTS four years later. Adjustment for serum androstenedione (p = 0.019) and dehydropiandrosterone (p = 0.037) attenuated the associations. Our study suggested that among individuals with low vitamin D status, the increase of the 25(OH)D level may be associated with a lowered risk of LUTS.